NMN partially rescues cuproptosis by upregulating sirt2 to increase intracellular NADPH - Yingying Zhang; Shuting Qiu; Shihan Shao; Yuejia Cao; Yu Hong; Xianrong Xu; Xuexian Fang; Chunhong Di; Jun Yang; Xiaohua Tan (Scientific Reports, 2024)
Abstract Cuproptosis is characterized by lipoylated protein aggregation and loss of iron–sulfur (Fe–S) proteins, which are crucial for a wide range of important cellular functions, including DNA replication and damage repair. Sirt2 and sirt4 are lipoamidases that remove the lipoyl moiety from lipoylated proteins using nicotinamide adenine dinucleotide (NAD+) as a cofactor. However, to date, it is not clear whether nicotinamide mononucleotide (NMN), a precursor of NAD+, affects cellular sensitivity to cuproptosis. Therefore, in the current study, cuproptosis was induced by the copper (Cu) ionophore elesclomol (Es) in HeLa cells. It was also found that Es/Cu treatment increased cellular DNA damage level. On the other hand, NMN treatment partially rescued cuproptosis in a dose-dependent manner, as well as reduced cellular DNA damage level. In addition, NMN upregulated the expression of Fe-S protein POLD1, without affecting the aggregation of lipoylated proteins. Mechanistic study revealed that NMN increased the expression of sirt2 and cellular reduced nicotinamide adenine dinucleotide phosphate (NADPH) level. Overexpression of sirt2 and sirt4 did not change the aggregation of lipoylated proteins, however, sirt2, but not sirt4, increased cellular NADPH levels and partially rescued cuproptosis. Inhibition of NAD+ kinase (NADK), which is responsible for generating NADPH, abolished the rescuing function of NMN and sirt2 for Es/Cu induced cell death. Taken together, our results suggested that DNA damage is a characteristic feature of cuproptosis. NMN can partially rescue cuproptosis by upregulating sirt2, increase intracellular NADPH content and maintain the level of Fe-S proteins, independent of the lipoamidase activity of sirt2.